Social media communication : concepts, practices, data, law and ethics - Lipschultz, Jeremy Harris, 1958- (New York, NY : Routledge, 2015)
'In Social Media Communication: Concepts, Practices, Data, Law and Ethics, Jeremy Harris Lipschultz presents a wide-scale, interdisciplinary analysis and guide to social media. Examining platforms such as Twitter, Facebook, LinkedIn, Pinterest, Youtube and Vine, the book explores and analyzes journalism, broadcasting, public relations, advertising and marketing. Lipschultz focuses on key concepts, best practices, data analyses, law and ethics--all promoting the critical thinking professionals and students need to use new networking tools effectively and to navigate social and mobile media spaces. Featuring contemporary case studies, essays from some of the industry's leading social media innovators, and a comprehensive glossary, this practical, multipurpose textbook gives readers the resources they'll need to both evaluate and utilize current and future forms of social media'--
Includes bibliographical references and index.
Keywords: Social media; Social networks; Online social networks; Social media -- Law and legislation; Social media -- Moral and ethical aspects